PEMODELAN DAN SIMULASI TAHAP AKHIR SINTERING KERAMIK - Himawan , Chrismono
Abstract : Some physical phenomena occur in the final stage of solid-sate sintering of ceramics, such as grain growth, pore coalescence, and others originated by pore inhomogeneity, have significant role on the development of sintered products microstructure. To produce materials of high density and fine grain size, those phenomena could not be neglected. This research deals with an effort to develop a mathematical models of the final stage sintering that includes those substantial phenomena. Models are based on classical diffusion model proposed by Coble [1961]. Two kinds of models have been established, i.e. models for homogenous compact and models for compact with Iarge pores. Some predictive mechanisms controlling the densification rate and the grain growth rate are also introduced. Models have been tested by utilizing the kinetics data of sintering provided in literature. Aluminum oxide ceramic is chosen to represent the system of solid-sate sintering. The most suitable models is then used to assess some parameters and variables involved in the final stage through computer-based simulations. Some conclusions can be noted here on the reference of simulation results : (1) The homogeneity of ceramic compact is very important to achieve a reliable microstructure of sintered products, (2) Sequential steps to find diffusion mechanisms that have been used successfully for undoped ceramic in this research are suggested to be conducted as a preliminary step to asses the influence of dopant on solid-state sintering behavior, and (3) Influencing the diffusion coefficients and the grain boundary mobility in the absent of changing the diffusion mechanism is considered to be an opportunity to gain better ceramic microstructure.